Mexican cinema : reflections of a society, 1896-2004 - Mora, Carl J. (Mcfarland, 2012)
"Arranged chronologically, this updated and revised edition covers the scope of Mexican cinema. The main films and their directors are discussed, together with the political, social and economic context of the times. Appendices offer selected filmographies and useful addresses"--Provided by publisher.